The Effect of Teachers’ Pedagogical Competence and Technology Utilization on Students’ Learning Outcomes in Public Elementary Schools - Apik Soraya; Bukman Lian; Muhammad Juliansyah Putra (Universitas Muhammadiyah Purwokerto, 2026)
This study aimed to analyze the effect of teachers’ pedagogical competence on students’ learning outcomes, to examine the effect of technology utilization on students’ learning outcomes, and to investigate the simultaneous effect of teachers’ pedagogical competence and technology utilization on students’ learning outcomes. This research employed a quantitative approach. The sample consisted of 98 teachers from five public elementary schools in Kalidoni District, Palembang City. Data were collected through questionnaires and documentation. Instrument validity was tested using construct validity, while reliability was measured using Cronbach’s Alpha. The prerequisite analyses included tests of normality, homogeneity, linearity, and homoscedasticity. Data analysis was conducted using quantitative descriptive analysis with multiple regression techniques. The results indicated that (1) teachers’ pedagogical competence had significant effect on students’ learning outcomes in public elementary schools in Kalidoni District, Palembang City; (2) technology utilization had significant effect on students’ learning outcomes; and (3) Teachers’ pedagogical competence and technology utilization simultaneously have a stronger and more significant effect on students’ learning outcomes than the effect of each variable individually in public elementary schools in Kalidoni District, Palembang City, with an R Square value of 0.912, indicating that 91.2% of the variance in students’ learning outcomes is explained by both variables, while the remaining 8.8% is influenced by other factors.